Cardiac autonomic dysfunction in survivors of childhood acute lymphoblastic leukemia: The St. Jude Lifetime Cohort Study. Issue 7 (8th May 2020) - Christoffersen, Lindsey; Gibson, Todd M.; Pui, Ching‐Hon; Joshi, Vijaya; Partin, Robyn E.; Green, Daniel M.; Lanctot, Jennifer Q.; Howell, Carrie R.; Mulrooney, Daniel A.; Armstrong, Gregory T.; Robison, Leslie L.; Hudson, Melissa M.; et al.
Abstract: Background: Cardiac autonomic dysfunction (CAD) is possible following treatment for childhood cancer. The aims of our analyses were to compare the prevalence of CAD between adult survivors of childhood acute lymphoblastic leukemia and controls, compare exercise response among survivors with and without CAD, and identify treatment‐related risk factors for CAD. Procedure: Participants were treated for childhood acute lymphoblastic leukemia at St. Jude Children's Research Hospital between 1980 and 2003 ( N = 338). A comparison group matched for race/ethnicity, age, and sex was also recruited ( N = 325). Resting heart rate (HR) was assessed via electrocardiogram, and heart rate recovery (HRR) and exercise capacity were evaluated with submaximal cardiopulmonary exercise testing. Results: CAD was present in 33.7% of survivors and 27.6% of controls ( P = 0.09). Although mean resting HR did not differ between survivors and controls (74 ± 12 vs 72 ± 12 beats per minute (bpm), P = 0.07), survivors had lower mean HRR than controls (22 ± 9 vs 25 ± 10 bpm; P < 0.001). Survivors with CAD had lower peak exercise tolerance (25.7 ± 6.5 vs 21.2 ± 4.9 mL/kg/min, P < 0.001) than those without. Survivors treated with cyclophosphamide in combination with vincristine ≥38 mg/m 2 and/or glucocorticoids ≥10 000 mg/m 2 were 1.56 (95% CI 1.09‐2.24) times more likely to have CAD than those without this treatment. Obese survivors were 1.78 (95% CI: 1.31‐2.40) times more likely to have CAD than nonobese survivors ( P < 0.001). Conclusion: CAD was present in over one third of survivors and was associated with lower exercise capacity. Obese survivors and those exposed to cyclophosphamide with high doses of vincristine and/or corticosteroids were at greatest risk.